Allee effects drive the coevolution of cooperation and group size in high reproductive skew groups. (20th February 2020) - Lerch, Brian A; Abbott, Karen C
Abstract: The evolution of cooperation between conspecifics is a fundamental evolutionary puzzle, with much work focusing on the evolution of cooperative breeding. Surprisingly, although we expect cooperation to affect the population structures in which individuals interact, most studies fail to allow cooperation and population structure to coevolve. Here, we build two models containing group-level Allee effects (positive density dependence at low group sizes) to study the coevolution of cooperation and group size. Group-level Allee effects, although common in cooperatively breeding species, remain understudied for their evolutionary implications. We find that a trait that affects group size can cause increased cooperation to be favored evolutionarily even in a group with complete reproductive skew. In particular, we find a single evolutionarily stable attractor in our model corresponding to moderate helpfulness and group size. In general, our results demonstrate that, even in groups with complete reproductive skew, Allee effects can be important for the evolution of cooperation and that the evolution of cooperation may be closely linked to the evolution of group size. Further, our model matches empirical data in African wild dogs ( Lycaon pictus ), suggesting that it may have an application in understanding social evolution in this endangered species. Abstract : Models of social evolution often assume a population structure and do not allow it to coevolve with cooperative behavior. But, in groups where each individual can reproduce, group size can coevolve with cooperation and lead to cooperation being favored. Such work has not been extended to groups with a single reproductive breeding pair. We show that introducing a trait constraining group size leads to the evolution of cooperation in groups with only one reproductive pair in a model with high breeding uncertainty.